Environmental perception of ecosystem services and degrading impacts to the mangrove by the urban population, Babitonga Bay-Brazil - Juliana da Motta Bustamante; Rodolfo Coelho Prates; Marta Jussara Cremer (Ambiente & Sociedade)
Abstract The mangroves of Babitonga Bay are rich ecosystems that provide numerous ecosystem services (ES). Such recognition is fundamental for their preservation. However, several threats affect the supply of these ES. With the objective of analyzing the environmental perception of the coastal urban population regarding the SE of the mangroves and the degrading impacts on the ecosystem, questionnaires were applied to residents of neighborhoods that suffered historical losses of mangroves in the municipality of Joinville - SC, Brazil (Boa Vista and Comasa). Quantitative and qualitative analyzes (content analysis) were performed. The results indicate that cultural (leisure) and provision services were perceived as the most important by the population, followed by the disposal of waste, the filling of the mangrove soil embankmentand the lack of sanitation. Our findings highlight the need to promote environmental education, basic sanitation, and the creation of leisure spaces to alleviate pressure on the studied coastal wetland.